Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12917-020-02388-2
|View full text |Cite
|
Sign up to set email alerts
|

Meningioma and associated cerebral infarction in three dogs

Abstract: Background: In dogs, meningiomas mostly cause chronic progressive clinical signs due to slow tumor growth. Case presentation: In contrast, three dogs were presented with the history of chronic generalized tonic-clonic seizures and peracute deterioration with sudden onset of neurological deficits in accordance with an extensive unilateral forebrain lesion. Magnetic resonance imaging examinations of the dogs revealed a well-delineated extraaxial T2W hyperintense mass in the rostral forebrain with homogeneous con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Comparison of focal-side cerebral blood flow (CBF) and cerebral blood volume (CBV) between the experimental group and the control group on day 30 and day 1 showed that CBF content on day 30 was 38.2 (mL/100 g/min), while CBF content in the control group was 36 (mL/100 g/min); the differences were statistically significant ( p < 0.05). Compared with the control group, CBF and CBV of the affected side of the experimental group increased, and blood flow and volume recovered, which was similar to the results of Frank et al [ 20 ]. It indicated that AI-segmented MRI images had a good coincidence between the diagnosis results of acute cerebral infarction and clinical comprehensive diagnosis results.…”
Section: Discussionsupporting
confidence: 88%
“…Comparison of focal-side cerebral blood flow (CBF) and cerebral blood volume (CBV) between the experimental group and the control group on day 30 and day 1 showed that CBF content on day 30 was 38.2 (mL/100 g/min), while CBF content in the control group was 36 (mL/100 g/min); the differences were statistically significant ( p < 0.05). Compared with the control group, CBF and CBV of the affected side of the experimental group increased, and blood flow and volume recovered, which was similar to the results of Frank et al [ 20 ]. It indicated that AI-segmented MRI images had a good coincidence between the diagnosis results of acute cerebral infarction and clinical comprehensive diagnosis results.…”
Section: Discussionsupporting
confidence: 88%
“…A total of 84 patients who experienced acute cerebral ischemia from March 2019 to February 2021 in our hospital were selected. The inclusion criteria were as follows: Patients (1) Aged 57–82 years; (2) diagnosed with unilateral acute ischemic cerebral infarction (diagnostic criteria of the Fourth National Academic Conference on Cerebrovascular Diseases in 1996)[ 4 ]; (3) with dizziness, vomiting, limb numbness, and headache as the main clinical manifestations; (4) who were hospitalized within 24 h of the onset of the disease and who underwent MRI; and (5) who provided informed consent before the relevant examination. The exclusion criteria were as follows: Patients with (1) Cerebrovascular hemorrhagic diseases (hypertensive cerebral hemorrhage, aneurysm, arterial malformation); (2) intracranial tumors; (3) a history of craniotomy; (4) a history of acute myocardial infarction and had an implanted pacemaker placed less than 3 mo previously; (5) cochlear implants and other such complications; (6) mental illness and hyperthyroidism; and (7) a history of drug allergy.…”
Section: Methodsmentioning
confidence: 99%
“…Although the disease process is progressive, the gradual onset of more subtle vision deficits is not recorded by owners. To increase survival time in dogs with brain tumors, it might be worthwhile for surgical resection and fractionated radiotherapy [ 72 ], although these tumors are associated with significant morbidity [ 73 ]. Rossmeisl et al (2013) [ 74 ] reported that the prognosis for dogs with palliatively treated primary brain tumors is poor.…”
Section: Different Scenarios Concerning the Euthanasia Requestmentioning
confidence: 99%